Surface Plasmon stimulated photoemission process at metal gratings : Theory and Experiments. (August 2015) - Sadou, A; Raynaud, M; Duchateau, G; Geoffroy, G; Martin, P; Jouin, H
Synopsis: Energy spectra related to the Surface Plasmon enhanced electron emission process at gold surfaces have been measured and calculated. Comparisons between theoretical and experimental spectra allow to obtain the amplitude of the Surface Plasmon field.